PENGARUH DESTINATION IMAGE DAN PERCEIVED QUALITY TERHADAP SATISFACTION SERTA BEHAVIOR INTENTION - Naira, Pristi Yeza; Pujiastuti, Eny Endah; Sadeli, Sadeli (Jurnal Ilmu Administrasi dan Bisnis, 2019)
The success of a destination is not determined by internal characteristics, but depends on the environment in which the destination operates like tourists. Literature about travel and perceived service quality, satisfaction and behavior intention, but the relationship between these variables has not been thoroughly investigated with the object of research in the tourist village. The purpose of this study is to determine and explain the effect directly between destination image, perceived value on satisfaction and behavioral intention. Data were collected through a questionnaire about the tourism village of Brayut tourism district of Sleman DIY. A total of 116 questionnaires were returned and data were analyzed using SEM AMOS. The results showed that there was a direct influence between destination image, perceived value on satisfaction and behavioral intention. Keywords : destination image, perceived quality, satisfaction, behavior intention.